Food Cue Reactivity and the Brain-Heart Axis During Cognitive Stress Following Clinically Relevant Weight Loss - Rauch, Henri G. Laurie; Hume, David J.; Howells, Fleur M.; Kroff, Jacolene; Lambert, Estelle Victoria (Frontiers in Nutrition, 2019)
Successful weight loss maintainers are more vulnerable to stress induced eating and may succumb when allocating cognitive resources to an attention-demanding task that overstretch their ability to monitor dietary restraint. The aim of our study was to determine what effect visual food cues had on the brain-heart axis of women who maintained clinically relevant weight loss compared to women who had never weight cycled during laboratory induced cognitive stress. A clinical weight loss group (CWL, n = 19) and a BMI-matched control group (CTL, n=23) completed modified Stroop tasks that either included (Food Stroop) or excluded visual food cues (Office Stroop) of high calorie food items. Heart rate, respiratory rate, and EEG were recorded. Both Groups: Heart rates were lower and inter-beat intervals (R-R), log High Frequency Power (log HF power) and log of Total Power in participants’ cardiac spectrograms were significantly greater during the Food compared to Office Stroop tasks. CWL participants: During the Food Stroop task the latencies of the P200 ERP at the C3 electrode upon Stroop cue exposure were positively associated with the log HF power values in their cardiac spectrograms (r = 0.64, p < 0.01). No such relationship was found during the Office Stroop task nor in the CTL participants. In conclusion the participants’ cardiovascular responses evoked by the Stroop Tasks were significantly dampened during the Food relative to Office Stroop tasks. This suggests that food cues ameliorate peripheral stress reactivity during cognitive stress and may be a neurobiological driver for stress induced eating. There was a significant brain-heart association during early attention processing in the CWL participants during the Food Stroop task, but not during the Office Stroop task, nor in CTL participants.